Rasool-e-Akram S.A.W.W ki Siyaasat-e-Kharija - Prof Muhammad Sadeeq Qureshi (Jhelum Qantara Publications, 1978)
A book on Political strategy of Prophet Muhammad S.A.W.W
Keywords: Prophet Muhammad S.A.W.W Political strategy